2015
DOI: 10.2196/jmir.5152
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Survey Findings Inform Patients’ Experiences in Using Secure Messaging to Engage in Patient-Provider Communication and Self-Care Management: A Quantitative Assessment

Abstract: BackgroundSecure email messaging is part of a national transformation initiative in the United States to promote new models of care that support enhanced patient-provider communication. To date, only a limited number of large-scale studies have evaluated users’ experiences in using secure email messaging.ObjectiveTo quantitatively assess veteran patients’ experiences in using secure email messaging in a large patient sample.MethodsA cross-sectional mail-delivered paper-and-pencil survey study was conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 15 publications
2
39
2
Order By: Relevance
“…Healthcare providers who are aware of their patients’ eHealth literacy skillsets can better recommend relevant health information resource or train them to use technology-based resource [9]. Improving patients’ skills using Internet-based health resources, such as interactive discussion forums and secure messaging platforms [10], may enhance patients’ health-related knowledge and self-efficacy and self-manage their chronic condition(s).…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare providers who are aware of their patients’ eHealth literacy skillsets can better recommend relevant health information resource or train them to use technology-based resource [9]. Improving patients’ skills using Internet-based health resources, such as interactive discussion forums and secure messaging platforms [10], may enhance patients’ health-related knowledge and self-efficacy and self-manage their chronic condition(s).…”
Section: Introductionmentioning
confidence: 99%
“…The eHEALS has also been used with a wide variety of samples, including schoolchildren and adolescents [13,45,52,56,64,66,67], parents [48,69], university students [23,42], adults comprising different age groups of a wide age range [16,58,60] and adults comprising solely older generations [34,43,54], as well as veterans [46,70], patients [44,49-51,53,71], caregivers [47], and health service providers [21,59]. The scale has been used with very small (<100) sample sizes [34,42,43,45,59], as well as studies comprising several thousand respondents [48,58,60,66].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that portals are a preferred method for contacting a physician[13], and due to the increased access and general anonymity that online communication affords, patients are more likely to clearly express their thoughts[35] and to disclose potentially embarrassing issues[36]. Our findings indicate that both patients and providers are engaging in patterns of communication via online messaging that may differ from what has traditionally occurred in face-to-face encounters.…”
Section: Discussionmentioning
confidence: 75%
“…However, in-person communication is associated with greater communication apprehension than electronic modes of communication[11]. Electronic communication can be less intimidating than in-person encounters, and studies have shown that it is now patients’ preferred method for contacting a physician[12, 13]. …”
Section: Introductionmentioning
confidence: 99%